Can English Camp Predict The Interest of Mountain Tribe Children in Binaiya in Learning English? - Nurlaila Sopamena; Muhammad Kashai Ramdhani Pelupessy; Abdul Azis Mahu; Nurmalita Sopaheluwakan (Journal of English as A Foreign Language Teaching and Research, 2025)
The toughest challenge for education policy makers is to provide programmes that can help mountain tribe children to be immersed into the English learning process, so that they can overcome their learning difficulties. This research highlights this by providing an English camp for mountain tribe children at the foot of Binaiya mountain, Central Maluku, Indonesia. Through a quasi-experiment on a group of 13 people, it was found that English camp strongly predicted the interest of mountain tribe children in Binaiya in learning English (p = 0.009). This is because English camp can help children immerse themselves into the learning process and facilitate their self-determination and comfort. However, the limitations of this study are that it did not fully control for threat factors and present a comparison group. Therefore, the recommendation for future researchers is to pay attention to this, and make self-determination and comfort as moderator and/or mediator variables in predicting English camp on interest in learning English.